Biochemical and Anthropometric Nutritional Assessment in Children Infected with COVID-19: A Cross-sectional Study - Ibrahim, Hoda Atef Abdelsattar; Helmy, Eatematd; Amin, Aya; Mahmoud, Dina (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Severe acute respiratory syndrome has led to a pandemic of coronavirus disease 2019 (COVID-19). Malnutrition either biochemically or anthropometrically is a well-known risk factor for COVID-19 and may be the vice versa Objectives : To investigate the prevalence of malnutrition in children infected with COVID-19 through evaluating the nutritional biomarkers such as serum electrolytes, serum albumin and hemoglobin together with the anthropometric assessment. Methods: A cross sectional study that was conducted at ElMatria Teaching Hospital for all children admitted with confirmed COVID-19 over a period of 6 months from 1st February 2021 to the end of July, 2021. Nutritional biochemical evaluation included serum electrolytes particularly the potassium and other nutritional biomarkers such as serum albumin and hemoglobin. Nutritional anthropometric evaluation depended on BMI (body mass index), the height/length, weight for length and weight for height..The prevalence of malnutrition esp. hypokalemia was the main outcome. Results: Hypokalemia was present in 21.8% of the study participants . Other nutritional biomarkers were found as hyponatremia, hypocalcemia , hypophosphatemia, hypomagnesemia were detected in 49.1% , 38.2%,21.8% and 34.5% of the study subjects respectively. Anthropometric malnutrition was present in most of the enrolled children with COVID-19 in the study (65.5 % (n= 36) )through which overweight and obese children occupied a greater percentage. Conclusion: Malnutrition either biochemically or anthropometrically could be linked to COVID-19 in children. COVID-19 could have negative outcomes on the nutritional status such as electrolytes disturbances. Both malnutrition and COVID-19 are considered synergistic associations Keywords: Malnutrition. COVID-19. Children. Hypokalemia. Obesity